A self-converted strategy toward multifunctional composites with laser-induced graphitic structures. (20th October 2020) - Wang, Guantao; Wang, Yong; Luo, Yun; Luo, Sida
Abstract: Laser-induced graphene (LIG) has provided a facile and effective strategy for graphene formation via one-step laser scribing on polymer structures. However, the direct utilization of LIG toward multifunctionalization for high-performance fiber-reinforced polymeric composites (FRPs) is rarely explored. Aiming to integrate the laser-induced graphitic structure (LIGS) with FRPs through the most facilitated approach, herein, we innovatively report a self-converted strategy for manufacturing multifunctional LIGS-hybridized FRP-composites (LIGC). By incorporating the laser irradiation process on either pristine or fully-cured epoxy prepregs at different stages of composite manufacturing, two paths of LIGS formation have been naturally developed to respectively implant the designable graphitized patterns interlaminarly or superficially. Benefiting from systematic processing-dependent-structural analysis, diversified properties of LIGC can be modulated for simultaneously achieving the optimized electrical conductivity ( 0.74 kΩ/sq) as well as the negligible mechanical degradation (<1.58%) compared with neat composites. By virtue of bimodally selectable processes along with tunable properties, the novel LIGC structure is highly advantageous with multifunctions, including sensing (monitoring resin-cure, mechanical-deformations, & hazardous liquids), self-defensing (de-icing & fire retardancy), and energy-harvesting (supercapacitors). Graphical abstract: Image 1